DEVELOPMENT OF TECHNOLOGY FOR DRY EXTRACT OF GRASS HARROW THE FIELD - A. M. SAMPIEV; N. A. DAVITAVYAN; V. V. STAROVEROVA (Кубанский научный медицинский вестник, 2017)
The urgency of developing a drug laxative action of grass harrow the field in the form of dry extract. The technology of dry extract of grass harrow using the method of vacuum filtration of extraction. A quantification of the active ingredients – phenolic compounds of a dry extract of grass harrow causing its laxative effect. The total content of phenolic compounds (isoflavones, flavonoids, phenolcarbonic acids) in phytopreparations harrow was about 25 %.